Dairy Cows Naturally Infected with Bovine Leukemia Virus Exhibit Abnormal B- and T-Cell Phenotypes after Primary and Secondary Exposures to Keyhole Limpet Hemocyanin - Frie, Meredith C.; Sporer, Kelly R. B.; Benitez, Oscar J.; Wallace, Joseph C.; Droscha, Casey J.; Bartlett, Paul C.; Coussens, Paul M. (Frontiers in Veterinary Science, 2017)
Bovine leukemia virus (BLV) is a retrovirus that is highly prevalent in US dairy herds: over 83% are BLV-infected and the within-herd infection rate can be almost 50% on average. While BLV is known to cause lymphosarcomas, only 5% or fewer infected cattle will develop lymphoma; this low prevalence of cancer has historically not been a concern to dairy producers. However, more recent research has found that BLV+ cows without lymphoma produce less milk and have shorter lifespans than uninfected herdmates. It has been hypothesized that BLV infection interferes with normal immune function in infected cattle, and this could lead to reduced dairy production. To assess how naturally infected BLV+ cows responded to a primary and secondary immune challenge, 10 BLV+ and 10 BLV- cows were injected subcutaneously with keyhole limpet hemocyanin (KLH) and DDA. B and T cell responses were characterized over the following 28 days. 56 days after primary KLH exposure, cows were re-injected with KLH and B and T cell responses were characterized again over the following 28 days. BLV+ cows produced less KLH-specific IgM after primary immune stimulation; demonstrated fewer CD45R0+ B cells, altered proportions of CD5+ B cells, altered expression of CD5 on CD5+ B cells, and reduced MHCII surface expression on B cells ex vivo; exhibited reduced B cell activation in vitro; and displayed an increase in BLV PVL after KLH exposure. In addition, BLV+ cows had a reduced CD45R0+ γδ+ T cell population in the periphery; and demonstrated a greater prevalence of IL4-producing T cells in vitro. All together, our results demonstrate that both B and T cell immunity is disrupted in BLV+ cows, and that antigen-specific deficiencies can be detected in BLV+ cows even after a primary immune exposure.